Reproductive performances of Boe, Kacang and Boerka does - Simon Elieser; Sumadi .; G Suparta; Subandriyo . (Indonesian Center for Animal Research and Development (ICARD), 2012)
Does reproduction performance could be expressed by her ability to give birth and to give milk to their kids during the pre-weaning period. This study was aimed to evaluate the reproductive performance of Boer, Kacang and Boerka does; and was carried out for two years at Research Institute for Goat Production, Sungei Putih. The materials used were goats owned by the institute. The parameters observed were: litter size, parity of does, preweaning mortality, kidding interval and sex ratio of kids. The rate of reproduction of the does was estimated using Amir and Knipscheer methods and were statistically analyzed using General linear model. Results showed that litter size and kidding interval of Boer goats were higher (P < 0.05) then that of Kacang goats, while the Boerka goats was in between. The mortality at preweaning of Boer goats was lower (P < 0.05) then that of Kacang goats, while the Boerka goats was in between. The percentage of kid sex ratio of three breeds were fluctuated. Parity of does had significant effect on all reproduction traits (P < 0.05) except for sex ratio of kids. The does reproduction was smallest at the first parity, and increased with the increase of parity from one to four, and then decreased in subsequent parities. The highest does reproduction rate was found in the Boerka (1.82), followed by Boer (1.80) and Kacang (1.80). It is concluded that the reproductive performance of the three breed female goat was relatively the same. Key Words: Performance, Reproductive, Boer, Kacang